(untitled) (Mustansiria Dental Journal, 2018)
One of the main considerations of the investment materials is there adequacy to expand thermally and by setting expansion to compensate for casting shrinkage, and any investment having zero setting expansion and adequate thermal expansion, by the use chemical additives and water instead of colloidal silica suspension would eliminate all inaccuracies arises from distortion of the wax pattern due to setting expansion. Thus the aim of this study was to evaluate the influence of two alkaline metals as additives K2SiO3 and Na2SiO3, to enhance the thermal expansion of phosphate – bonded investment without the use of colloidal silica suspension. Three mixtures (45 samples) were prepared, mixture I of 15 samples contains Na2SiO3, Mixture II of 15 samples contains K2SiO3 in percentages of (0.5, 1.0, 1.5, 2.0, and 2.5) for each three samples of both (mixture I & II), and mixture III of fifteen samples as a control group without additives. The thermal expansion measured by vitreous silica dilatometer from 100 – 950 ºC. The results showed that the highest mean of thermal expansion was in samples that contain Na2SiO3, and the lowest mean of thermal expansion was in the control group samples.